2002
DOI: 10.1046/j.1365-2982.2002.00334.x
|View full text |Cite
|
Sign up to set email alerts
|

The 13C‐octanoic acid breath test: validation of a new noninvasive method of measuring gastric emptying in rats

Abstract: Currently available rat models for measuring gastric emptying are hampered by the necessity to kill the animals at the end of each experiment, which makes repetitive testing impossible. We have developed and validated a noninvasive test model, adapted from the 13C-octanoic breath test in humans, for repetitive measurements of gastric emptying in rats. Male Wistar rats were trained on a fixed protocol to eat a piece of pancake doped with 1 microg 13C-octanoic acid after 12 h fasting, and to stay thereafter in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 20 publications
2
27
0
Order By: Relevance
“…Wyse and colleagues used 13 C-octanoic acid breath tests in ponies (20) and dogs (21) to evaluate gastric emptying. For smaller experimental animals, Schoonjans and coworkers (6) reported the use of a breath test with 13 Coctanoic acid in rats placed in metabolic air-tight cages.…”
Section: Discussionmentioning
confidence: 99%
“…Wyse and colleagues used 13 C-octanoic acid breath tests in ponies (20) and dogs (21) to evaluate gastric emptying. For smaller experimental animals, Schoonjans and coworkers (6) reported the use of a breath test with 13 Coctanoic acid in rats placed in metabolic air-tight cages.…”
Section: Discussionmentioning
confidence: 99%
“…1-3) Thereafter breath tests using 13 C-labeled compounds have been used in laboratory animals for evaluating physiological function, such as gastric empying 4,5) or liver function. 6) Recently, the present authors reported simple and noninvasive breath test system for monitoring gastric emptying by using 13 C-labeled acetic acid in conscious rats.…”
Section: )mentioning
confidence: 99%
“…By using this method, gastric emptying time can be indirectly measured by monitoring the 13 CO 2 concentration in the expired air after a 13 C-labeled substance, such as acetic acid or octanoic acid, was ingested and absorbed from the duodenum.1-3) Thereafter breath tests using 13 C-labeled compounds have been used in laboratory animals for evaluating physiological function, such as gastric empying 4,5) or liver function. 6) Recently, the present authors reported simple and noninvasive breath test system for monitoring gastric emptying by using 13 C-labeled acetic acid in conscious rats.…”
mentioning
confidence: 99%
“…In vitro studies indicated that alcohol and its metabolite acetaldehyde can inhibit the expression of tight junction protein, resulting in increased permeability [83,86] Additionally, alcohol can impair microtubule cytoskeleton in intestinal epithelial cells by inducing nitric oxide overproduction and oxidation/ nitration of cytoskeletal proteins [87]. A recent study has demonstrated that the changes to tight junctions occur in liver cirrhosis of mixed aetiology [88], and are not limited to alcoholic liver disease. More importantly, the reduction in tight junction proteins appears to relate to the disease severity, and is more pronounced in decompensated patients as compared to compensated patients [3].…”
Section: Gastrointestinal Permeability In Cirrhosismentioning
confidence: 99%